Perspective of Marxism-leninism on the Similarities and differences between Religion and Socialism - Trong Tha, Ha (International Journal of Psychosocial Rehabilitation, 2020)
Religion is the result of human creativity. As a form of social consciousness, religion is determined by and reflects social existence. However, religion also has its own active role. By reflecting the society, religion desires for people to be happy and leads people to do good through profound human viewpoints. This article presents the perspective of Marxism-Leninism on the similarities and differences between religion and socialism. On that basis, the author comments on the evolution of religion in the development of human society, especially in the condition of socialism.